The US presidential Elections: A Democratic Dilemma and a Renewed Electoral Ordeal - Ibrahim , Ahmad Fawwaz (Dirasat: Human and Social Sciences, 2024)
Objectives: This study aimed at understanding the representation gap in the presidential elections through the working mechanism of the Electoral College. Methods: This study used the analytical approach through historical analysis of facts of the American presidential elections and statistical data for a set of results of those elections. Results: The study results showed the depth of the representation gap that appeared in the results of the previous presidential elections will increase the emergence of challenges in the 2024 elections and beyond, and will not stop the outcomes of the 2020 elections that showed serious defects in American democracy. Despite the improvement of laws regulating this Electoral College work, most of them pour horizontally and are not affected in terms of its creation by excluding the majority and throughout time regardless of the amount of (vertically) suggested amendments on college or its replacement, it has remained trapped in the American Congress offices. Conclusion: The study noted that demands to reform or abolish the American Electoral College have increased recently. These demands emanated from deepening the representation gap leading to the legitimacy of the President of the United States of America.